Asymptomatic congenital tracheal stenosis. Issue 7 (1st August 2019) - Sumi, Toshiyuki; Ikeda, Takumi; Nakata, Hisashi
Key message: Congenital tracheal stenosis (CTS) is often identified by characteristic wheezes and cyanosis in childhood. However, an asymptomatic progression to adulthood is rare. Asymptomatic latent CTS cases with a mild degree of stenosis may exist. Abstract : We describe a rare case of asymptomatic congenital tracheal stenosis in an adult with a mild degree of stenosis.